Only after looking at your solution was I able to figure that your really meant....
(w-2)/(w-7) - (w+1)/(w+7) + (w-77)/(w^2-49)
= [(w^2 + 5w - 14) - (w^2 - 6w - 7) + w-77 ]/[(w+7)(w-7)]
= (12w - 84)/[(w+7)(w-7)]
= 12(w-7)/[(w+7)(w-7)]
= 12/(w+7) , w ≠ 7 (or else we divided by zero)
Could someone please explain this problem to me?
I will show you what I have so far.
Perform the indicated operations and simplify.
w-2/w-7-w+1/w+7+w-77/w^2-49
I made it to this step and now I can't figure out what to do next.
w^2+w-14/(w+7)(w-7) + w^2-6w-7/(w+7)(w-7) + w-77/(w+7)(w-7)=(w^2+w-14)+(w^2-6w-7)+(w-77)/(w+7)(w-7)= 4w-98/(w+7)(w-7).
This is where I'm lost at. I can't seem to figure out the end result.
Thanks for the help.
2 answers
Thanks but I figured out where I made my mistake and got the answer.